Differential host susceptibility to intracerebral infections with Candida albicans and Cryptococcus neoformans. - Blasi, E (1993)
To investigate the immune defense mechanisms employed against fungi in the brain, mice were experimentally infected by intracerebral inoculation of Candida albicans or Cryptococcus neoformans. Parameters such as median survival time and numbers of yeast cells in the brains were assessed for naive and immunomodulated mice. We found that no mice survived either C. albicans or C. neoformans challenge at doses of > or = 10(6) yeast cells per mouse. However, when the inoculum size was decreased (< or = 10(5) yeast cells per mouse), C. albicans was no longer lethal (100% survival), whereas 100 and 70% of the mice still succumbed to challenge doses of 10(4) and 10(3) C. neoformans yeast cells, respectively. Pharmacological manipulation and transfer experiments revealed that the myelomonocytic compartment had a minor role against C. neoformans but was deeply involved in the control of intracerebral C. albicans infection. By counting the number of yeast cells in the brains of naive and immunomodulated animals, we established that, unlike C. albicans, C. neoformans remained essentially in the brain, where massive colonization and damage occurred whether naive or immunomodulated defense mechanisms were employed by the host. Overall, these data suggest that the differential role of the myelomonocytic compartment, together with the diverse tropisms of the two fungi, can explain the different development and outcome of intracerebral C. albicans and C. neoformans infections.